2020
DOI: 10.14740/jocmr4311
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acceptance and Commitment Therapy in Substance Use Disorders: A Review of Literature

Abstract: Background: Acceptance and commitment therapy (ACT) is a form of behavioral therapy that teaches people to learn to accept rather than avoid challenging situations in their lives. ACT has shown to be an intervention with great success in the reduction of various mental disorders and substance use disorders (SUDs). The core of ACT when used in SUD treatment is guiding people to accept the urges and symptoms associated with substance misuse (acceptance) and use psychological flexibility and value-based intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…MBIs have also been implemented in the context of behavioral and substance-related addictive disorders, and results have been very promising [20,21]. Two meta-analyses, however, concluded that MBIs are not of superior efficacy as already implemented treatment approaches [12,24]. As mindfulness research is still in its infancy, more longitudinal RCTs with large sample sizes are needed to confirm the clinical use in addictive disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBIs have also been implemented in the context of behavioral and substance-related addictive disorders, and results have been very promising [20,21]. Two meta-analyses, however, concluded that MBIs are not of superior efficacy as already implemented treatment approaches [12,24]. As mindfulness research is still in its infancy, more longitudinal RCTs with large sample sizes are needed to confirm the clinical use in addictive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 10 RCTs comparing ACT to other active treatments (e.g., TAU, CBT) found significant small effect sizes favoring ACT on substance use (g = .29 − .45) [5]. A more recent review of 22 studies concluded that ACT alone or in combination with other treatments was effective in reducing substance use [24].…”
Section: Efficacy Of Mbismentioning
confidence: 99%
“…The evidence-based treatment process specifically highlights the need for clinical engagement and shared decision-making with patient values and goals inherent in that process ( Gambrill, 2006 ; Melnyk et al, 2010 ; Hoffmann et al, 2014 ). Treatment around substance use that involves patient values has evidence for efficacy ( Osaji et al, 2020 ). Someone who, for example, is unsuccessfully using kratom to self-treat anxiety may be surprised to learn that there are evidence-based psychotherapies (e.g., cognitive-behavioral therapy) that are effective for doing the same.…”
Section: Best Practices In the Clinical Care Of People Who Use Kratommentioning
confidence: 99%
“…ACT processes such as acceptance and defusion can undermine the dominance of such contexts and reduce the likelihood of substance use. ACT may be effective in the treatment of addictions [ 132 , 133 ] by increasing psychological flexibility, i.e., the ability to choose value-guided behavior even in the presence of problematic thoughts and emotions. ACT aims to broaden an individual’s range of behavioral options when faced with symptoms, in this case by promoting alternative behaviors to BZD consumption.…”
Section: Acceptance and Commitment Therapy For Discontinuing Long-term Benzodiazepine Usementioning
confidence: 99%
“…Two reviews have confirmed the effectiveness of ACT in the treatment of substance use disorders (alcohol, tobacco, opioids, and metamphetamins) [ 132 , 133 ]. ACT has a significant effect on maintaining the abstinence rate.…”
Section: Acceptance and Commitment Therapy For Discontinuing Long-term Benzodiazepine Usementioning
confidence: 99%